Monitoring Compliance and Acceptability of Intermittent Preventive Treatment of Malaria Using Sulfadoxine Pyrimethamine after Ten Years of Implementation in Tanzania. (30th March 2017) - Ayubu, Mdetele B.; Kidima, Winifrida B.
Abstract : Intermittent preventive treatment using SP (IPTp-SP) is still a superior interventional approach to control malaria during pregnancy. However its rate of use has gone down tremendously in malaria endemic areas. This study forms part of a larger study aimed at monitoring the compliance of IPTp-SP policy in malaria endemic areas of Tanzania. Two cross-sectional studies were conducted in Dar es Salaam and Njombe Regions of Tanzania. Overall, 540 pregnant women and 21 healthcare workers were interviewed using structured questionnaires. This study revealed that 63% of women were not willing to take SP during pregnancy while 91% would only take it if they tested positive for malaria during antennal visits. 63% of the interviewed women did not know the recommended dose of SP required during pregnancy, despite the fact that 82% of the women were aware of the adverse effect of malaria during pregnancy. It was found out that 54% of pregnant women (30–40 weeks) took single dose, 34% took two doses, and 16% did not take SP at the time of interview. It was also found that SP was not administered under direct observed therapy in 86% of women. There was no significant relationship between number of doses received by pregnant women and antenatal clinic (ANC) start date (r 2 = 0.0033, 95% CI (−0.016 to 0.034)). However positive correlation between drug uptake and drug availability was revealed (p = 0.0001 ). Knowledge on adverse effects of placental malaria among pregnant women was significantly associated with drug uptake (OR 11.81, 95% CI (5.755–24.23), p = 0.0001 ). We conclude that unavailability of drugs in ANC is the major reason hindering the implementation of IPTp-SP.